Patung Dewa Ruci Dalam Perspektif Budaya Bali - I Nyoman Linggih (Institut Seni Indonesia Denpasar, 2007)
Statue is one form of fine arts which is known as the aesthetic experience which come out from the forms of three dimension. Ruci /Nawa Ruci is the form of God or Ida Shang Hyang Widhi in a form of one and only. The Ruci statue has an aesthetic appearance physically. The Ruci statue is a complete group, the united of one figure to another figure from point of view form structure and the existence of statue composition. The Ruci statue has functions: sacred function, ritual/ceremony function, religious aesthetic function. The Ruci statue is symbolize as a snake or dragon in the ocean wave which describe all commitment of human life in the real world which always bring the flows of human life uncertain. Bhima who is known as a micro cosmos figure or as a human being who looking for his true self and wants to find himself. Ruci/ Acintya represent in the statue is presented the sense of “Me” belong to every human life. So that the real phenomenon of Ruci statue is about dialog between soul (atma) with the highest soul (paramatma)in order to find out the real meaning.